Um narrador e sua criatura: uma leitura do duplo em Um sopro de vida, de Clarice Lispector - Ivan, Maria Eloísa de Souza (2015)
Started in 1974, the posthumous book Um sopro de vida (pulsações), by Clarice Lispector, came to public in 1978. Written "in agony" (Borelli, 1981), the work resumes introspective density featuring Clarice's writing, repeats the existential paradox life and death so recurrent in her work, reveals itself as a work of beginning and end, one and multiple, finally, leading us by several known ways, or not. Recognizing that reading involves an empathetic relationship and motivated to continue the master's research, also about Clarice's work, I felt compelled to face the reading of such a dense work and to seek still little trodden paths. Thus, in this project, we have resumed aspects which have not been explored in our master's research for not being part of the objectives of that work, but which were perceived as relevant for further study. Among these aspects, we mention the manifestation of the double as a structural element of Um sopro de vida (pulsações) narrative, 1978, chosen as the corpus of this research. The theme of the double has always been present in the Western culture, varying according to the historical moment. Renovated in modernity, the myth of the double also reveals the man as a shattered person, having as one of its possible representations the division of the "I" in an "ego" and an "alter ego". To better understand the relationship of the double with the work, we can say that many centuries separate the Greek legend, told by Aristophanes, and from the book Um sopro de vida (pulsações), by Clarice Lispector. The legend seeks to explain the need of human beings to ever get the half that fulfills them; Clarice's work embodies, among others, the man's questioning in search of himself, reflecting on the "who am I?", "who is the other?". In this way, describing and analyzing the figure of the narrator-Author, establishing a counterpoint between narrator-Author/Ângela Pralini and observing the process of building the character like an image that is constituted "by" the other makes up the specific objectives of this study; it is also our purpose to investigate and analyze the effects of discursive meanings that recover the images of God, of the "you", of the mirror and the death in relation to the narrator-Author and Ângela Pralini. Guiding us, then, through reflections, by Rank, Clément Rosset, Bravo, Bakhtin, among others, the research presented here proposes, as a questioning, to investigate how the image of the double emerges as a structuring element of Clarice's narrative, more specifically in Um sopro de vida (pulsações), and to what extent this discursive feature manifests itself in the narrator-Author/Ângela Pralini counterpoint, his double, also investigating how this narrator is manifested in personal oscillations, in the expansion of the narrating function, in the lexical choices, in the adopted bias: who is the double of whom?